Stability of Algerian black seed (Nigella sativa L.) in relation to antimicrobial activity under different storage conditions - Ahamad Bustamam, Muhammad Safwan (2016)
The present study is an effort to determine the stability of the main volatile constituents of Nigella sativa seeds stored under several conditions. Nine storage conditions which were set based on the ecological abiotic effects of air, humidity, heat and light, with six replicates each were prepared and analyzed with Headspace (HS)-Gas Chromatography-Mass Spectrometry (GCMS) for three time points of initial (1st day – 0), 14th (1) and 28th (2) day of storage. A targeted multivariate analysis of PCA revealed that the stability of the whole seeds main volatile constituents were better than those of the ground seeds in relation to the selected ecofactors. The findings showed that the air, humidity, heat and light are suggested to be in reverse relationship with the stability of N. sativa seeds. Based on the study, the condition which showed minimal changes towards the environmental effects is that whole seeds stored in a transparent vial with nitrogen gas flush. The disc-diffusion test antimicrobial activity of the different stored conditions of N. sativa samples were conducted on several human pathogens wherein the whole seed stored in limited air content (condition B and C) and exposed to light gave more promising results. However, the minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) results showed no significant difference among all conditions after 28 days storage. The antimicrobial metabolites were identified through correlation of antimicrobial activities (disc-diffusion test) with N. sativa whole seeds of different storage conditions by supervised multivariate data analysis (MVA) of Orthogonal Partial Least Squares (OPLS), which suggested that 7 significant variables responsible as chemical markers. Furthermore, the predictability of antimicrobial activity based on the whole seed model was done on 10 new observations of known GC-MS data whereby only fresh whole seed (MEOH) sample was positively predicted. Based on the present findings, N. sativa seeds need suitable storage parameters to preserve the volatiles for less quality deprivation.